1986
DOI: 10.1002/eji.1830161109
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a regulatory role of the T8 (CD8) antigen in antigen‐specific and anti‐T3‐(CD3)‐induced lytic activity of allospecific cytotoxic T lymphocyte clones

Abstract: The functional role of the T8 antigen of human T cells was studied by inhibition with anti-T8 monoclonal antibodies (mAb) of the cytotoxic action of T8+ cytotoxic T lymphocyte clones (CTL). All clones were allospecific and directed against HLA-B7. The ability of seven different anti-T8 mAb to inhibit the cytotoxicity of these alloreactive CTL clones corresponded with their avidity for a particular target cell. The lysis of cross-reactive antigen-bearing target cells was more readily blocked by anti-T8 mAb than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
3
11
1
2
Order By: Relevance
“…Previous studies have shown that anti-CD8 Abs retain their effects in the absence of a pMHCI/CD8 interaction (26,(53)(54)(55). In this study, we confirm that the enhancing effects of OKT8 on HLA A*0201 tetramer on-rate at the cell surface are still apparent in the context of CD8-null MHCI molecules (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that anti-CD8 Abs retain their effects in the absence of a pMHCI/CD8 interaction (26,(53)(54)(55). In this study, we confirm that the enhancing effects of OKT8 on HLA A*0201 tetramer on-rate at the cell surface are still apparent in the context of CD8-null MHCI molecules (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, the lysis of LH cell is totally inhibited by anti-CD3 and anti-CD8 mAb, whereas lysis of the B27.1 target LG15 was only partially inhibited by anti-CD8 mAb (Table 3). This phenomenon was also observed recently with another CTL clone [29]. This result may be interpreted in two ways: (a) blocking by anti-CD8 mAb reflects differences in avidity in a more sensitive way than cold target inhibition experiments, and (b) inhibition of lysis by anti-CD8 mAb would not only reflect avidity of effector-target interaction but would have additional effects on post-binding steps, as has been previously suggested [29,301.…”
Section: Discussionsupporting
confidence: 65%
“…This suggests that many ofthe differences between the PCR and the cDNA sequences are artefacts of the cDNA analysis (21). Our analysis of 10 PCR HLA-B7 cDNA sequences does not support the suggestion that JY expresses two distinguishable HLA-B7 alleles (22).…”
contrasting
confidence: 73%